Analysis of Water Pollution in the Kapuas River Due to Illegal Gold Mining (IGM) Activities - Yuris Sutanto; Elvi Derina Safitri; Andi Ihwan; Hasanuddin Hasanuddin; Kukuh prasetyo (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2026)
Illegal gold mining (IGM) activities, utilizing mercury (Hg) in their processing, have the potential to pollute and impair river functions. Therefore, a study was conducted to analyze the water quality status of the Kapuas River due to IGM activities in Sekadau Regency based on physical and chemical parameters. Water quality status was determined by comparing observations at the research site with quality standards using the Pollution Index (PI) method. In this scientific paper, the physical parameters tested are turbidity, conductivity, total dissolved solids (TDS), total suspended solids (TSS), and water temperature. In contrast, the chemical parameters tested are pH, dissolved oxygen (DO),  Iron (Fe), Hg, lead (Pb), and manganese (Mn). Based on the research results, the parameters that meet the quality standards are TDS, TSS, pH, Hg, Pb, and Mn. Parameters not meeting the quality standards are turbidity, conductivity, water temperature, DO, and Fe. The PI value obtained was (5.25 ± 0.008). Based on the PI value, the water quality status was classified as moderately polluted. The TSS parameter exhibits a radial pattern from the pollution source, indicating that the measured TSS values decrease with increasing distance from IGM activity.